The extent of tonal events: intonational hat patterns in Chilean Spanish - Brandon M A. Rogers (Estudios de Fonética Experimental)
Within the past 15 years there has been a dramatic increase in the popularity of studies of Spanish intonation. Despite this surge, relatively little attention has been given to the variety of Spanish spoken in Chile. As a result, there is still much that is not known about the prosodic properties and patterns of Chilean Spanish intonation. The current study examines a previously undocumented plateau, or hat, pattern that does not appear in any of the known literature regarding Chilean or general Spanish intonation. The pattern was determined to consist of four different portions: an initial valley or dip to a lower F0 level in which all internal material was maintained at the same low tonal level, a sharp rise to a high tonal level, a high plateau in which all plateau internal material was maintained at the same high tonal level and finally an utterance final fall. The current investigation is the first known phonetic documentation of the Chilean hat pattern and likewise is a preliminary attempt at a phonological analysis within the current Autosegmental Metrical (AM) theoretical framework. Finally, the hat pattern highlights potential shortcomings and limitations of the AM approach to intonational phonology, namely how tonal events are defined.